2012
DOI: 10.1128/aac.05823-11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antimicrobial Resistance among Clinical Isolates of Bacteroides fragilis Group in Canada in 2010-2011: CANWARD Surveillance Study

Abstract: Clinical isolates of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 15 publications
6
55
0
Order By: Relevance
“…As shown in this finding that these antimicrobials may not be very effective, as about 30% of the ETBF strains examined were resistant. In conformity with the results obtained by other investigators [10,11], we found cefoxitin resistance in ETBF to be very low (7.4%). From this study, it appears that the most effective antimicrobials for ETBF-mediated infection could be imipenem and chloramphenicol.…”
Section: Discussionsupporting
confidence: 95%
“…As shown in this finding that these antimicrobials may not be very effective, as about 30% of the ETBF strains examined were resistant. In conformity with the results obtained by other investigators [10,11], we found cefoxitin resistance in ETBF to be very low (7.4%). From this study, it appears that the most effective antimicrobials for ETBF-mediated infection could be imipenem and chloramphenicol.…”
Section: Discussionsupporting
confidence: 95%
“…However, as observed in a previous analysis of cIAI patients [27], the rates of clinical and bacteriological success achieved with moxifloxacin appear to be maintained well beyond the susceptibility breakpoint for key pathogenic species; this was observed during the long interval between 2000 and 2009 including each Phase III study period. Thus, despite recent warnings about the occurrence of resistant bacteria to major classes of antibiotics used to treat cIAIs that include not only fluoroquinolones but also carbapenems and piperacillintazobactam [29][30][31][32][33][34][35][36][37][38], our results may support the empiric use of antibiotics with a spectrum of activity covering the main causative organisms in cIAI patients with mild-to-moderate disease.…”
Section: Discussionmentioning
confidence: 57%
“…For clindamycin, 72% of our B. thetaiotaomicron isolates were resistant, compared to 17% of B. fragilis strains, while resistance in other Bacteroides and Parabacteroides species ranged from 26% to 42%. A recent study from Canada (16) Biapenem and biapenem-RPX7009 showed excellent activity against clinical isolates of Gram-positive and Gram-negative anaerobes that was comparable to that of meropenem. RPX7009 showed no antimicrobial activity when tested alone, and overall, there was no significant effect of RPX7009 on biapenem activity against anaerobic bacteria.…”
Section: Discussionmentioning
confidence: 99%